"Bring the numbers and stories together":Valuing events - Ren, Carina Bregnholm; Mahadevan, Renuka (Annals of Tourism Research, 2018)
This article introduces a Valuation Studies approach, in which valuation is seen as a social practice, to studying the outcomes of events. Drawing on material gathered around the Arctic Winter Games organized in Nuuk, Greenland in 2016, we exemplify how researchers working together across disciplinary and methodological boundaries can engage together with events stakeholders in making event values knowable beyond the confines of traditional evaluation. Analytically, we use Callons’ concepts on framing and overflows to exemplify alternative outcomes of events. We argue that a valuation approach offers an iterative understanding of event outcomes which encourages economics and constructivist research to collaborate on exploring event worth and making event overflows knowable and valuable.